Local stability analysis of mathematical model of Tuberculosis disease in Thailand - Puntani Pongsumpun (My University, 2021)
Tuberculosis (TB) is a contagious disease that is caused by Mycobacterium. It can be transmitted by air. When infected Tuberculosis speaks, coughs or sneezes. TB is present in the sputum droplets and rises into the air. Large aerosol particles often fall on the ground and dry out. The main symptom of tuberculosis is a chronic cough that lasts 2 weeks or more. Other symptoms may include loss of appetite, weight loss, fatigue, fever, chest pain, shortness of breath. This disease is transmitted between human. In this paper, we find the dynamical equations of this disease. We analyzed our mathematical model to find the equilibrium points of our mathematical model. Numerical solutions are analyzed to see the distribution of each group of population. The basic reproduction number of the disease is derived. The influence of each factor is analyzed.
Keywords: Tuberculosis Research and Epidemiology